Forgetting to Remember: Anamnesis and History in J. M. G. Le Clézio's Desert - Kathleen White Smith (Studies in 20th & 21st Century Literature, 1985)
Unlike most of Le Clezio's previous works. Desert has a specific historical framework. The story of the young boy Nour records the struggle of the Saharaoui people of the western Sahara to claim their land from the French invaders of the early twentieth century. A second narrative, set in the present, continues that story through the experiences of Lalla: unlike the story of her predecessor, the narrative in which she figures has no clear reference to the current, militant political situation established in the western Sahara by the independence movement known as Polisario. Containing both story and document, text and context, Le Clezio's novel offers a lesson in reading for history in a fictional text. Through the notion of anamnesis, a term prominent in Lacanian psychoanalytic theory as well as in mythic thought about memory, the two narratives come into focus as a single historical presence. Each story serves as a subtext for the other in an intratextual reading of the novel. The meaning of the early struggle for freedom emerges in the (re)telling of that history in the narrative of Lalla. Each new '"reading" of history is an interpretation that becomes itself a projection of a new story, a new form of the desire for meaning, through another narrative. Le Clézio's most recent novel is both an entry into history and a witness to the historical process.
Keywords: anamnesis; philosophy; memory; forgetting; Le Clezio; Desert; present; past; time; history; fiction; myth; psychoanalytic theory; intratextual reading; meaning